ՀՀ առևտրային բանկերում օտարերկրյա ներդրումների արդյունավետության գնահատումը - Սիմոնյան, Տարոն (Bulletin of Yerevan University G: Economics, 2019)
In this article, there have been investigated the main indicators of efficiency of foreign investments in the authorized capital of commercial banks of the Republic of Armenia. Particularly, the author has calculated the coefficients of profitability of foreign investments, dividend payment, etc. Also, there has been explored the influence of the devaluation of Armenian currency on the efficiency of foreign investments
Keywords: foreign investments, commercial banks, profitability of foreign investments, assessment of efficiency, dividend